MANFAAT PEMBERIAN JUS NANAS DAN MADU TERHADAP PENURUNAN NYERI DESMINORE PADA REMAJA PUTRI DI SMP YP SINGOSARI DELITUA - Insani, Septa Dwi; Hutabarat, Vitrilina; Krisna, Putri (INSTITUT KESEHATAN DELI HUSADA, 2023)
Dysmenorrhea is abdominal pain caused by uterine contractions and occurs during menstruation. Dysmenorrhea occurs due to increased secretion of prostaglandin F2a during the luteal phase of the menstrual cycle. Increased secretion of prostaglandin F2 alpha increases the frequency of uterine contractions and as a result can cause abdominal pain in women. The effects of primary dysmenorrhea include disruption of activities, such as absence from school or work, and limitations in social life, school performance, and athletic activities. Non-pharmacological pain management includes warm compresses, drinking lots of fluids, taking regular exercise breaks, consuming nutritious food, pain relief activities such as yoga, and using herbal medicine supplements which are effective in reducing menstrual cramps. Community service was carried out at YP Singosari Delitua Middle School with a total of 20 respondents. According to the results of most students who took part in consultations at YP Singosari Deli Tua Junior High School regarding the effect of pineapple juice and honey in reducing menstrual pain in young women, the level of knowledge is still low due to lack of socialization by providing education regarding the effectiveness of pineapple juice and honey in reducing menstrual cramps. , it is hoped that students can handle this dysmenorrhoea